Tradition Of Money Panai' And The Values Of Islamic Education In The Marriage Of The Bugiss Ethnic Group In The Community Of Manimbaya Village, Balaesang Tanjung District, Donggala Regency - Azisa, Wafik (Syntax Literate, 2025)
Uang panai' in the Bugis tribal marriage tradition, as a barometer of triggering the birth of various problems among the community, especially the youth because of its high value. Problem formulation: 1) what is the tradition of money panai' at the Bugis ethnic wedding in Manimbaya village, Balaesang Tanjung District, Donggala Regency?; 2) what are the values of Islamic education in the implementation of the tradition of money panai' at Bugis ethnic weddings in Manimbaya village, Balaesang Tanjung District, Donggala Regency?. This research aims to find out the form of the process of the tradition of money and the values of Islamic education that are hidden in this culture, as a chain of scientific development. Using a qualitative research model of a phenomenological approach with observation, interview and documentation data collection techniques and using Moustakas and Creswell data analysis techniques. Based on the existing procedures, the results were obtained: 1) that in the implementation of the tradition of money panai' there are 3 stages, namely mammanu'-manu', madduta mallino and mamppasiarekeng; 2) that the implementation of the tradition of money panai' is interpreted to contain Islamic values, namely; chastity, mutual respect and appreciation, appreciation for women, accuracy or prudence, responsibility and solidarity and consensus. Thus, the implication of this study states that the tradition of money panai' is an ancient philosophy (ancestors) in this case a philosophy of values with a philosophical meaning that has been in line with Islamic law, namely logical, aesthetic, ethical and religious. Thus, its existence lies in the individual, making the value the main benchmark of assessment in determining the amount of money and not in the nominal number. In line with this, it is hereby clear that the tradition of money can be carried out and does not contradict Islamic sharia because there is a minimum standard that is not burdensome and does not degrade both parties in this case as perpetrators in marriage.